The issues of Berenice II, an iconographic exception - Nothnagel Vivas, Katharina; Vico Belmonte, Ana (Eikón / Imago, 2026)
In 2016, the National Archaeological Museum (MAN) in Madrid acquired an octodrachm of Berenice II bearing the name of Arsinoe II at a public auction. The primary reason for this acquisition was the coexistence of iconographic and epigraphic references to two distinct personalities on the same coin. This peculiarity in Ptolemaic coinage, in addition to perpetuating an unprecedented iconographic model for representing Lagid queens, presupposes the need for numismatic research to examine its communicative function. Through iconographic analysis, this study seeks to unravel the message conveyed by this coinage. The motives that led Berenice II to portray herself in the manner of Arsinoe are not only related to issues of succession and consolidation of power but also to personal reasons stemming from family conflict. Berenice II preferred to associate herself with her paternal Ptolemaic lineage rather than her maternal Seleucid line— constituting clear evidence of the union of two kingdoms, the Ptolemaic realm and Cyrenaica, into a single state.